2019
DOI: 10.1371/journal.pone.0224655
|View full text |Cite
|
Sign up to set email alerts
|

EPILAT-IRA Study: A contribution to the understanding of the epidemiology of acute kidney injury in Latin America

Abstract: IntroductionEpidemiology of acute kidney injury (AKI) is highly dependent on patient characteristics, context and geography. Considering the limited information in Latin America and the Caribbean, we performed a study with the aim to contribute to improve its better understanding.MethodsObservational, prospective, longitudinal, multinational cohort study addressed to determine risk factors, clinical profile, process of care and outcomes of AKI in the region. Patients meeting KDIGO AKI definition were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
4
20
0
7
Order By: Relevance
“…Pediatric patients with AKI reach their maximum KDIGO stage during the first week after diagnosis [9,16,25,26]. In our study, most of the patients included reached their maximum KDIGO stage on day one after admission to PICU and this may be explained by several potential factors: patients included came from rural areas, had varying degrees of malnutrition, and presented insurance-related barriers to health care in agreement with previous recent reports from Latin America [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pediatric patients with AKI reach their maximum KDIGO stage during the first week after diagnosis [9,16,25,26]. In our study, most of the patients included reached their maximum KDIGO stage on day one after admission to PICU and this may be explained by several potential factors: patients included came from rural areas, had varying degrees of malnutrition, and presented insurance-related barriers to health care in agreement with previous recent reports from Latin America [21].…”
Section: Discussionsupporting
confidence: 89%
“…In a recent survey carried out by SLANH in Latin America, hemodialysis was the main approach to RRT and its selection was guided mainly by economic and organizational regional reasons [21]. However, there would be strong variation among and within countries.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Several patients received more than one type of RRT. Reasons for initiation of RRT were electrolyte and/or acid base disturbances (70%), fluid overload (54%), and solute control (48%) [6].…”
Section: Renal Replacement Therapy For Acute Kidney Injury In Latin Amentioning
confidence: 99%
“…AKI was community-acquired in 62% of patients, with dehydration, shock and nephrotoxic drugs being the most common causes. Renal replacement therapy (RRT) was performed in 29% of cases, and the incidence of all-cause in-hospital mortality was 26.5%( 3 ). Preliminary and unpublished data from the Latin American Society of Nephrology and Hypertension (SLANH) AKI Committee registry of AKI in COVID-19 patients, which has enrolled 393 subjects so far, showed that more than 50% of patients were female, the median age was 60 (IQR 48-71), 36% of patients developed proteinuria and 17% presented with hematuria.…”
mentioning
confidence: 99%